The facilitating effect of identical objects in visual working memory - Ren, Guofang; Ma, Nan; Lei, Ming (Frontiers in Psychology, 2023)
According to the associative network of memory representations proposed by embedded processes models, the links between related memory representations were automatically established, which rendered these representations more easily activated. The present study adopted color recall tasks to explore whether the memory performance of identical objects was enhanced via the strengthening links between them, producing facilitating effect of identical objects. In Experiment 1, the number of identical items was manipulated. The results evidenced the facilitating effect, which was positively related to the number of identical objects. Experiment 2 modulated the spatial location of identical objects, which suggested that the facilitating effect was absent when two pairs of identical objects were located diagonally. Furthermore, Experiment 3 suggested that the facilitating effect was observed for the identical items which were presented in the second and fourth quadrants, rather than the first and third quadrants. Together, these results evidenced the facilitating effect of identical objects, which, however, was affected by spatial bias.